Extraversion and anterior vs. posterior DMN activity during self-referential thoughts - Knyazev, Gennady G. (Frontiers in Human Neuroscience, 2013)
Recent studies show that fronto-posterior electroencephalogram (EEG) spectral power distribution is associated with personality. Specifically, extraversion is associated with an increase of spectral power in posterior cortical regions that overlap with the posterior default mode network (DMN) hub and a decrease of spectral power in anterior regions that overlap with the anterior DMN hub. Although there is evidence that dopaminergic neurotransmission may be involved, psychological processes that underlie these associations remain unclear. We hypothesize that these processes may have something to do with spontaneous self-referential thoughts. Specifically, we hypothesize that in extraverts self-referential thoughts may be associated with an increase of spectral power in the posterior DMN hub, whereas in introverts they may be associated with an increase of spectral power in the anterior DMN hub. After spontaneous EEG registration, participants were asked to fill in a questionnaire describing their thoughts during the registration. An item describing self-referential positive expectations (SRPE) was used to measure individual differences in the intensity of these processes. Source localization and independent component analyses were applied to EEG data to reveal oscillatory activity associated with the anterior and the posterior DMN hubs. Hierarchical regression analysis showed a significant interaction between extraversion scores and anterior vs. posterior DMN alpha activity in predicting individual differences in SRPE scores. In extraverts, high SRPE scores were associated with an increase of alpha power in the posterior DMN hub, whereas in introverts they were associated with an increase of alpha power in the anterior DMN hub. Results are discussed in terms of differential involvement of the two DMN hubs in self-related reward processes in extraverts and introverts.